Partnering with consumers to develop and evaluate a Vietnamese Dementia Talking-Book to support low health literacy: a qualitative study incorporating codesign and participatory action research. Issue 9 (26th September 2016) - Goeman, Dianne; Michael, J; King, J; Luu, Huy; Emmanuel, Claire; Koch, S
Abstract : Objective: The aim of the Vietnamese Dementia talking-book was to address low health literacy in older people of Vietnamese background living with dementia through the provision of an online resource to help individuals, their families and carers better understand and manage this condition and provide information about available dementia services. Design: This qualitative study used codesign and participatory action research to develop and refine the talking-book in consultation with expert stakeholders, a consumer advocacy group and the Vietnamese community to assess its utility and ensure cultural and linguistic appropriateness and relevance. Participants: 59 members of the Vietnamese community, 11 stakeholders from community health services and ethnic agencies, consumer advocacy groups and the research team participated in the codesign and refinement of the talking-book. 22 members of the Vietnamese community appraised the final product. Setting: Vietnamese community planned activity groups in the Western, Northern and Southern suburbs of Melbourne, Australia. Results: Our codesign study outlines the process required to develop a Vietnamese Dementia Talking-Book resource partnering with consumers and expert stakeholders to identify consumer need, selection of the content and appropriate language level, construction of the book, measuring acceptability of the talking-book, modification based on feedback and production and dissemination. Feedback on the final version of the talking-book revealed widespread consensus that the book enhanced the knowledge of members of the Vietnamese community in regard to understanding dementia and navigation and accessing of available services. Conclusions: This free internationally available online Vietnamese Dementia Talking-Book facilitates improved dementia-related health literacy in the Vietnamese community. The book also serves as a tool to facilitate the provision of care to Vietnamese people living with memory loss by assisting health professional staff to develop relationships with Vietnamese clients, their families and carers in a culturally appropriate manner.